Caracterização e modelagem do crescimento da copa e do incremento de árvores isoladas de Cedrela fissillis Vell. - Cavalli, Jean Pierre (2013)
On the growth evaluation of the open-grown trees was selected 57 samples, of which were mensuration many morphometric variables from digital photographs in software AutoCAD and dendrometrics variables in bole increment extracted in diameter breast height (DBH). The development of this research was to described the singular dimensions and recover crown and bole growth from open-grown Cedrela fissilis, corresponding to period 2007-2011, and build mathematical equations to described the growth of variable crown diameter (CD), mantle of the crown (MC), crown diameter in relative heights (CDrh) and periodic annual increment in basal area (PAIb). In the annual lengthening (AL) were observed minimum, maximum and median annual values of 3.0, 91.0 and 32.4 cm, respectively. As well as, serie correlations, determined by Pearson (r = 0.76 a 0.86; Pr<.0001), with higher lengthening connected to the lower orders of branching. In periodic lengthening (PL), corresponding to the period of 2007-2011 there were values of up to 1.82 m, found in diameter class 30-40, with a coefficient of variation (CV) up to 67.67%, checked in diametric class > 60. To model growth construction 35 trees were selected from 57 initially sampled considering it crown and bole conditions, having been discarded sample of the > 60 diametric class. To the mantle of the crown variable the model NLMC=b0+b1*(1/DBH)+b2*(DBH²) has good adjust (R²adj.=0.92; VC=6.12%). The equation to annual lengthening of the crown, ALC=b0+b1*(NLCAI)+b2*(DBH) showed adjustment and precision (R²adj.=0.50; VC=35.95%), it explaining until 50% total variance, but with higher percent residual. With similar precision, the model adjusted to crown growth in diameter, CGD=b0+b1*(NLCAI), had statistical precision defined to R²adj= 0.44 and VC=36.25%, with higher VC resulted from the higher variance in samples. To the CDrh the adjust was represented to R²adj.=0.58 and VC=52.41%, had been defined the model NLCDrh=b0+b1*(NLDBH)+b2*(1/hi²)+b3*(DBH²), with the results of residual evaluations didn t submit normality distribution and homogeny variance. The adjust to CAIb equation showed good statistical precision (R²adj.=0.66; VC=11%), it explaining until 66% total variance from model NLCAIb=b0+b1*(DBH)+b2*(h/d). On the increment descriptive analyses it observed high periodic annual increment in diameter (PAId) and PAIb in the 25, 35 and 45 cm diameter class. The PAId medium, minimum and maximum values correspond to 3.6 cm, 0.7 cm and 7.3 cm. At the 35 and 45 cm class it observed 95.6 and 75.5 PAIb average, respectively. All of the diameter classes it was observed current annual increment in diameter (CAId) higher 2.5 cm. The crown growth reviews from the open-grown trees demonstrated that the crown growth rhythmic and its correlation with the bole increments it turn possible to build growth models characterized to good adjust and statistical efficiency, wherever, it should be stratification methods based in site informations. The methodology analyses with digital photography also showed good precision and practicality, it can be widely used to review singular and open-grown trees.